End-To-End QoS Network Design Quality of Service for Rich-Media and Cloud Networks - Szigeti, Tim; Hattingh, Christina; Barton, Robert; Briley, Kenneth (Cisco Press, 2013)
Annotation
Keywords: Computer networks -- Design and construction; Computer networks -- Management -- Quality control; Réseaux d'ordinateurs; Gestion; Qualité; Contrôle; Computer networks; Design and construction